PENGARUH DANA PERIMBANGAN DAN BELANJA MODAL DAERAH TERHADAP IPM, TPT, TPAK DAN PERSENTASE PENDUDUK MISKIN - Slamet Widodo; Kiki Zakiah (Pusat Kajian Anggaran, 2022)
The purpose of this research is to analyze the effect of fiscal balance funds and regional capital expenditure on the Human Development Index (IPM), Open Unemployment Rate (TPT), Workforce Participation Rate (TPAK), and Percentage of Poor Population in municipalities/cities. The research used secondary data from 309 municipalities/cities for the period of 2020-2021 from the Central Agency of Statistics (BPS), the Ministry of Finance, and other related institutions. The research methodology used Regression of the Data Panel with Fixed Effect Model and Ordinary Least Square estimation. The results of the research show that the Fiscal Balance Fund and regional capital expenditures variables significantly influence the IPM, TPT, TPAK, and percentage of the poor population in a negative/positive direction.